Imaging white matter diffusion changes with development and recovery from brain injury. - Bosnell, R; Giorgio, A; Johansen-Berg, H (2008)
PURPOSE: This study reviews the application of diffusion tensor imaging (DTI) to the study of developmental and pathological changes in brain white matter. The ability to measure and monitor such changes in vivo would provide important opportunities for charting disease progression and monitoring response to therapeutic intervention. This study first reviews the use of DTI in studying normal human brain development. It goes on to illustrate how DTI has been used to provide insights into recovery from damage in selected brain disorders. CONCLUSIONS: It is concluded that potential clinical applications of DTI include: (i) monitoring pathological change, (ii) providing markers that predict recovery and allow for individual targeting of therapy, (iii) providing outcome measures, (iv) providing measures of potentially compensatory structural changes and (v) improving understanding of normal brain anatomy to aid in interpretation of the consequences of localized damage.